New species of black corals (Cnidaria:Anthozoa: Antipatharia) from deep-sea seamounts and ridges in the North Pacific - Opresko, Dennis M.; Wagner, Daniel (Zootaxa, 2020)
Three new species of antipatharian corals are described from deep-sea (677–2,821 m) seamounts and ridges in the North Pacific, including Antipathes sylospongia, Alternatipathes venusta, and Umbellapathes litocrada. Most of the material for these descriptions was collected on expeditions aboard NOAA Ship Okeanos Explorer that were undertaken as part of the Campaign to Address Pacific Monument Science, Technology, and Ocean Needs (CAPSTONE). One of the main goals of CAPSTONE was to characterize the deep-sea fauna in protected waters of the U.S. Pacific, as well as in the Prime Crust Zone, the area with the highest known concentration of commercially valuable deep-sea minerals in the Pacific. Species descriptions and distribution data are supplemented with in situ photo records, including those from deep-sea exploration programs that have operated in the North Pacific in addition to CAPSTONE, namely the Hawaii Undersea Research Laboratory (HURL), the Ocean Exploration Trust (OET), and the Monterey Bay Aquarium Research Institute (MBARI).